2017
DOI: 10.1017/s0018246x16000613
|View full text |Cite
|
Sign up to set email alerts
|

RING ROAD: BIRMINGHAM AND THE COLLAPSE OF THE MOTOR CITY IDEAL IN 1970s BRITAIN

Abstract: Reconstructing Britain's cities to accommodate the 'motor revolution' was an integral part of urban renewal in the post-war decades. This article shows how opposition to urban motorways had a pivotal role in the retreat from urban modernism in the 1970s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…A mentalist conception of decisions, insofar as it obscures this importance of wider infrastructure via its focus on agential deliberation, therefore understates the importance of this issue, concentrating on relatively smaller-scale actions that center on the agent's psychology. An historical assessment will reveal that the role of policy in infrastructure, and transport more widely, has been far from passive or inert: It has been contingent, deliberate, and, if this word be allowed, intentional [98]. It is not by any means suggested that there are easy answers to the problems in transport, but by casting a light on the importance of infrastructure in addition to discrete individual motives as such, it is hoped that policy-makers will be encouraged to take a broader view of possible remedies.…”
Section: Discussionmentioning
confidence: 99%
“…A mentalist conception of decisions, insofar as it obscures this importance of wider infrastructure via its focus on agential deliberation, therefore understates the importance of this issue, concentrating on relatively smaller-scale actions that center on the agent's psychology. An historical assessment will reveal that the role of policy in infrastructure, and transport more widely, has been far from passive or inert: It has been contingent, deliberate, and, if this word be allowed, intentional [98]. It is not by any means suggested that there are easy answers to the problems in transport, but by casting a light on the importance of infrastructure in addition to discrete individual motives as such, it is hoped that policy-makers will be encouraged to take a broader view of possible remedies.…”
Section: Discussionmentioning
confidence: 99%
“…He was not in favour of large-scale plans which, he felt, were "often obsolete by the time they were put into effect" (Sutcliffe & Smith, 1974, p. 448) and the city had pre-war plans for slum clearance and road improvements (Manzoni, 1955). Post-war reconstruction to create a fully-functioning "motor city" occurred, but in a piecemeal fashion (Gunn, 2018). There were plans, but nothing comprehensive until the city belatedly responded to the legal requirement in the 1947 Act to prepare a city-wide Development Plan.…”
Section: The Examples Of Bath Birmingham and Hullmentioning
confidence: 99%
“…The "jealousy and disagreement between the city engineer and the city architect" (Ross, City Estates officer, interviewed in Sutcliffe, 1967Sutcliffe, -1969 certainly led to problems of implementation. Ultimately, later criticisms centred on how many urban dwellers' experiences of the new city were subordinated to the desires of overbearing transport systems, and a redeveloped centre built around cultures of leisure, consumption, and work (Gunn, 2018).…”
Section: The Examples Of Bath Birmingham and Hullmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Colin Buchanan in his famous report "Traffic in towns" from 1963 tried to take up environmental concerns into new concepts for urban automobility and infrastructure. 49 In Switzerland in the context of an environmental turn from 1970 onwards urban citizens increasingly resisted to new automobile infrastructural projects, as Haefeli has shown. 50 Parallel to these discourses throughout Europe from around 1970 onwards in West-Berlin also the general political context and the mode of governance substantially changed.…”
Section: Rearranging the Balances Of Power Within The Municipal Adminmentioning
confidence: 99%